Cattle ranching in Colombia: A monolithic industry? - Campuzano, Lorena; Triana Ángel, Natalia; Burkart, Stefan (Historia Ambiental Latinoamericana y Caribena - HALAC, 2022)
This article analyzes literature on the history of cattle ranching and agricultural innovation adoption in Colombia to understand how livestock production systems have evolved from the 1950s until today. Departing from new scholarship that has questioned the idea that cattle ranching has been only a land-grabbing strategy dominated by few elites, this article focuses on the adoption of improved pastures and the role of key institutions such as the CIAT on the transformation of practices and the shortcomings of technification. It shows that Colombia has had big transformations with the introduction of improved pastures, particularly Brachiaria, but these transformations did not translate into a radical change in the dominant extensive livestock production systems. Instead of promoting intensification, the adoption of Brachiaria has allowed producers to expand more, often resulting in large deforestation. One of the main contributions of this article is the analysis of economic, developmentalist, and institutional reports that are not often used to construct historical analysis. It can also serve to scholars interested on adoption of agricultural techniques.